Gymnastics Peripheral Circulation In Legs And Diabetes Mellitus Patients - Subandiyo Subandiyo; Handoyo Handoyo; Asrin Asrin (Jurnal Riset Kesehatan, 2012)
The aim of this study is to show the impact of leg exercise towards peripheral leg circulation of diabetes mellitus patients. This study was pre experiment with the design of pre and post test one group without control group design approach. Leg exercise was done in 3 times of 3 days continuously. The score of ABI was measured by blood pressure cuff and Doppler vascular, pre and post leg exercise. The research sample was taken with a total sampling technique. The number of respondent 40 diabetes mellitus patients at RSUD Purbalingga. Paired t-test was used to show the significant impact of leg exercise towards peripheral circulation of leg of diabetes mellitus patients. Based on the results of statistical analysis with paired t-test showed that the p-value is 0,001 smaller than the value of α (5 %) or 0,05. Thus, Ho is rejected and Ha accepted. The result revealed that an average score of ABI before leg exercise at 0.91 and after leg exercise at 1.00, respectively. Leg exercise can decrease peripheral leg circulation viewed from value Ankle Brachial Index (ABI) of diabetes mellitus patients.